Revitalisasi Permainan Tradisional: Sebuah Upaya Pembentukan Mental Anti Korupsi Anak Sejak Dini - Sriwati Sriwati; Herry Porda Nugroho Putro (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The era of technology has made the meaning of playing experience a significant shift. Play tends to be interpreted as a fun activity to relieve boredom.-based games Online in cyberspace eventually paralyze games in the real world, so that children are often trapped in meaningless pseudo games. Good games for children are those that can meet physical, intellectual, emotional and social development as found in traditional games. Therefore, maintaining the existence of traditional games is not just a matter of continuing the tradition, but a need to save children from being trapped in meaningless pseudo fun. This research was conducted using qualitative research methods. The type of research used is descriptive qualitative with the subjects of class III and IV SD Negeri Anjir Pasar Lama 1. Data collection techniques used in this study include interviews, tests and questionnaires. Furthermore, the data that has been collected is analyzed by data reduction, data presentation, and verification. The results showed that children's knowledge of traditional games was quite low, even most students only had knowledge of traditional games, but never played them. Traditional games contain meaningful learning and experiences that will lead children to keep trying to improve themselves, and become wiser so that they can be accepted by their playing environment. Therefore, revitalization Traditional games are important to do as an effort to form children's anti-corruption mentality from an early age